Morphological evaluation of canine oocytes recovered in different phases of the estrous cycle - Sánchez R., Alfonso (2015)
The aim of the study was to obtain and morphologically evaluate canine oocytes from females at different phases of the estrous cycle and to compare the proportions of oocytes potentially suitable for in vitro maturation (IVM). Ovaries of 24 bitches, 6 for each phase of the estrous cycle, were sliced to recover the oocytes. These were morphologically classified into fit and unfit oocytes for IVM. The largest proportion of oocytes fit for IVM (86.6%) was recovered from females in proestrus and estrus (p<0.01) and the largest quantity of oocytes fit for IVM per female (448.0 ± 52.7) was obtained in the estrus phase (p<0.01). It is concluded that the morphological assessment of oocytes indicated that the quality and quantity of oocytes recovered during the oestrus and proestrus phase of the oestrus cycle in terms of their potential use form IVM were better and higher than those obtained during the anestrus and diestrus phases.